2014
DOI: 10.1111/apm.12228
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TIM‐3 on CD4+ and CD8+ T cells in the peripheral blood and synovial fluid of rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is characterized by a chronic inflammatory process that targets the synovial lining of diarthrodial joints. TIM-3 plays a key role in the negative regulation of the immune response. In this study, we investigated the expression of TIM-3 on CD4+ and CD8+ T cells from systemic (peripheral blood) and local (synovial fluid) perspectives of RA. Level of TIM-3+ cells from peripheral blood and synovial fluid of patients as well as peripheral blood of healthy controls was measured by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
0
27
2
Order By: Relevance
“…Li et al observed increased levels of TIM-3 on CD4+ and CD8+ T cells in the peripheral blood of patients with rheumatoid arthritis (39), whereas our study showed no changes in TIM-3 in SSc T cell subsets, but did show an increase in NK cells ( Figure 1E). In lupus patients, the levels of TIGIT were found to be up-regulated on CD4+ T cells but reduced in CD8+ T cells, NK cells, and Treg cells (40), an expression pattern that does not match with our observations in patients with SSc ( Figure 1D).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Li et al observed increased levels of TIM-3 on CD4+ and CD8+ T cells in the peripheral blood of patients with rheumatoid arthritis (39), whereas our study showed no changes in TIM-3 in SSc T cell subsets, but did show an increase in NK cells ( Figure 1E). In lupus patients, the levels of TIGIT were found to be up-regulated on CD4+ T cells but reduced in CD8+ T cells, NK cells, and Treg cells (40), an expression pattern that does not match with our observations in patients with SSc ( Figure 1D).…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, serum levels of soluble forms of PD-1 and its ligand PD-L2 were recently shown to be elevated in SSc (14). Li et al describe increased TIM-3 on CD4 + and CD8 + T cells in peripheral blood from rheumatoid arthritis patients (39), while our data show no changes in TIM-3 in SSc T cell subsets, but an increase in NK cells (Fig. 1E).…”
Section: Discussioncontrasting
confidence: 64%
“…Programmed cell death-1 (PD1), an immunosuppressive co-stimulatory molecule proven to play a major role in suppressing immune responses, and its ligand, programmed cell death-ligand 1, were found to be elevated in the T cells of patients with RA [12,13]. T cell immunoglobulin domain- and mucin-domain-containing molecule-3 (Tim-3), which are inhibitory receptors, have been showed to be expressed on T cells with high levels and to be correlated with disease activity in patients with RA [14]. Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), a member of the immunoglobulin superfamily that can down-regulate T-cell function, was also reported to be decreased on T cells, and its dysfunction was identified as a potential cause for abnormal T cell activation in RA [16].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with rheumatoid arthritis (RA), Tim‐3 expression on CD4 + and CD8 + T cells in peripheral blood mononuclear cells (PBMCs) and synovial fluid was increased. But the percentage of Tim‐3 expression on peripheral CD4 + and CD8 + T cells was negatively correlated with disease severity, as measured by the disease activity score 28 (DAS28) of the patients . In addition, the level of Tim‐3 expression on T cells was also inversely correlated with plasma TNF levels.…”
Section: Tim‐3 Regulates Th1 and Ctl Responsesmentioning
confidence: 99%